Why Wouldn't They Be Reconciled? Corbyn's Leadership and the Recalcitrance of the Parliamentary Labour Party. Issue 2 (17th June 2021) - Gilbert, Jeremy
Abstract: One of the most striking features of Labour Party politics during the years of Jeremy Corbyn's leadership was the recalcitrant lack of cooperation that he received from many Labour MPs, even after his remarkable success in the 2017 general election. This article systematically examines a number of possible explanations for this behaviour, including genuine divisions within the party over the issue of institutional anti‐semitism and over the politics of Brexit. Ultimately, it concludes that the most plausible explanation for MPs' opposition to Corbyn is simply the lack of material motivation for many of Labour's elected representatives and officials to pursue the end of a Labour government led by a political faction with which they themselves are not aligned.